2008
DOI: 10.5483/bmbrep.2008.41.5.376
|View full text |Cite
|
Sign up to set email alerts
|

RNA silencing-mediated resistance is related to biotic / abiotic stresses and cellular RdRp expression in transgenic tobacco plants

Abstract: The discovery of RNA silencing inhibition by virus encoded suppressors or low temperature leads to concerns about the stability of transgenic resistance. RNA-dependent RNA polymerase (RdRp) has been previously characterized to be essential for transgene-mediated RNA silencing. Here we showed that low temperature led to the inhibition of RNA silencing, the loss of viral resistance and the reduced expression of host RdRp homolog (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The marked decrease in siRNA level caused by low temperature is probably because of inhibition in enzymatic activity and/or gene expression of the protein(s) that plays important roles in siRNA generation and/or amplification. In transgenic tobacco, expression of a gene encoding RDR is down-regulated at low temperature (Wu et al 2008). Unlike TM, in the highly CD-tolerant cultivar TR, accumulation of CHS siRNAs is weakly inhibited by low temperature, and consequently CHS siRNAs are accumulated in the seed coat.…”
Section: Full and Partial Seed Coat Pigmentation In Yellow Soybeanmentioning
confidence: 99%
“…The marked decrease in siRNA level caused by low temperature is probably because of inhibition in enzymatic activity and/or gene expression of the protein(s) that plays important roles in siRNA generation and/or amplification. In transgenic tobacco, expression of a gene encoding RDR is down-regulated at low temperature (Wu et al 2008). Unlike TM, in the highly CD-tolerant cultivar TR, accumulation of CHS siRNAs is weakly inhibited by low temperature, and consequently CHS siRNAs are accumulated in the seed coat.…”
Section: Full and Partial Seed Coat Pigmentation In Yellow Soybeanmentioning
confidence: 99%
“…Overall, the experiments indicate that ihp‐PTGS is able to confer broad‐spectrum resistance/immunity to PPV even at low temperature. Conversely, RNA silencing‐mediated virus resistance driven by aberrant viral sense gene constructs (S‐PTGS) was lost when transgenic plants were challenged at 15 °C (Szittya et al ., ; Wu et al ., ). Our results are in accord with and extend the recent findings of Hu et al .…”
Section: Resistance Analysis Of H‐utr/p1 68 Transgenic Plants Challenmentioning
confidence: 97%
“…In particular, the RNA silencing driven by the expression of intron-hairpin (ihp) constructs (ihp-PTGS) has been shown to consistently confer virus resistance in most T0 plants (Di Nicola-Negri et al, 2005;Smith et al, 2000). Nevertheless, it has been reported that some abiotic and biotic conditions, such as low plant growth temperatures (Szittya et al, 2003;Wu et al, 2008) and mixed viral infections, can break RNA silencing-mediated virus resistance (Di Serio et al, 2002;Hassani-Mehraban et al, 2009;Jørgensen and Albrechtsen, 2007;Mitter et al, 2003;Savenkov and Valkonen, 2001;Simon-Mateo et al, 2003), thus representing a possible limitation for the full applicability of this biotechnological strategy.…”
mentioning
confidence: 99%
“…It is mediated by a large network of interacting effector molecules, and connected to several parallel regulatory and signaling pathways. It affects, both directly and indirectly, cellular processes varying from the cell cycle regulation and chromatin structure maintenance to transcriptional and posttranscriptional regulation, to stress and hormonal signaling, and to developmental differentiation [1-5]. Thus, RNA silencing plays a central role in manifestation of the genetic information of different eukaryotes.…”
Section: Introductionmentioning
confidence: 99%